Negotiating authenticities in mediatized times. (June 2015) - Androutsopoulos, Jannis
Abstract: Drawing on the papers of the Special Issue on "Authenticity and normativity in social media", this discussion piece points out a number of key themes for research on authenticity in digital language practices. I argue that the theoretical backdrop provided by the deconstruction of authenticity in sociolinguistics must be complemented by taking into account the specific conditions of social media as a site of communicative action that is central to contemporary mediatized societies. In the new public spheres constituted in social media, the display of authenticity is a core value in the production of discourse for a personal public. Displays of authenticity in social media are made available to a networked public whose follow-up discourses can involve remarkable linguistic reflexivity and normativity. Constructions and negotiations of authenticity in social media are found to draw on multilingual repertoires. Their objects of normative assessment are registers of language, which form part of an indexical order that can draw on globally circulating as well as locally anchored semiotic elements. Research in this area is likely to benefit from polycentric and transmedia strategies, which enable researchers to follow actors and their authenticating practices across on and offline spaces.